A valuation of the pharmaceutical company Novartis AG - Coelho, Ana Catarina Filipe de Sousa (2020)
This dissertation valuates Novartis AG, a Swiss pharmaceutical company operating globally, listed both in SIX and NYSE. The purpose of this valuation is to provide readers a recent considerate investment recommendation based on the forecasted market share price of Novartis. Examining and understanding the pharmaceutical sector and Novartis’s financial information led to conducting a valuation using the DCF and reaching a target share price of USD 99.75, indicating Novartis’s worth at 31st December of 2019. To complement this decision, this dissertation included the Relative approach using the ratios EV/EBITDA and EV/Revenues. Due to the inconsistency of results found, the DCF was the chosen model to value the company. Regarding these inferences, the conducted sensitivity analysis and both approaches, it decided a BUY recommendation is the right choice.